2014
DOI: 10.1016/j.tips.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine ups and downs in vulnerability to addictions: a neurodevelopmental model

Abstract: Addictions are commonly presaged by problems in childhood and adolescence. For many individuals this starts with the early expression of impulsive risk-taking, social gregariousness and oppositional behaviors. We propose here that these early diverse manifestations reflect a heightened ability of emotionally salient stimuli to activate dopamine pathways that foster behavioral approach. If substance use is initiated, these at-risk youth can also develop heightened responses to drug-paired cues. Through conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
98
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 131 publications
(141 reference statements)
1
98
0
1
Order By: Relevance
“…Current scientific evidence shows that addiction and a co-occurring mental disorder are not separate disorders, but rather different, interacting, clinical conditions. They may occur simultaneously or sequentially, and may develop due to individual and environmental factors (Leyton & Vezina, 2014;Szerman & Martinez-Raga, 2015). 6.…”
Section: Ten-point Statementmentioning
confidence: 99%
“…Current scientific evidence shows that addiction and a co-occurring mental disorder are not separate disorders, but rather different, interacting, clinical conditions. They may occur simultaneously or sequentially, and may develop due to individual and environmental factors (Leyton & Vezina, 2014;Szerman & Martinez-Raga, 2015). 6.…”
Section: Ten-point Statementmentioning
confidence: 99%
“…A relationship has been clearly established between the activation of this meso-corticolimbic system and the release of dopamine in its target zones. [18,19] With the progress in imagery, in microdialysis experiments in animals and more recently in humans it has also been shown that all the substances described as "artificial paradises" are able to activate this pathway and trigger the release of dopamine. For instance, a link has been clearly established between the inducement of a euphoric effect by amphetamines and the release of dopamine it produces.…”
Section: Addiction: the Pharmacological Modelmentioning
confidence: 99%
“…26 The basis and meaning of these low DA responses, however, remain unclear. They could reflect neurotoxic effects in late-stage addictions, 27 heritable endophenotypes, conditioned inhibitory effects induced by cues that signal the absence of reward, 5,28 or some combination of these effects (e.g., initial predispositions aggravated by rapidly developing conditioned effects and laterstage neurotoxicity).…”
mentioning
confidence: 99%
“…5,28 In comparison, augmented striatal responses have been seen when high-risk individuals are tested in the presence of drug-paired cues. 5,13,28 Indeed, across stages of addiction, striatal DA release is induced by drug-paired cues alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation